“Maria Maria”: o percurso co(n)textual de uma recategorização pela via ressignificada da teoria / “Maria Maria”: the co(n)textual path of a recategorization by the resignified pathway of the theory (Revista de Estudos da Linguagem, 2020)
Resumo: O presente estudo nasceu de dois objetivos centrais que se retroalimentam. O primeiro é discutir o estatuto atual da teoria da recategorização compreendido pela dimensão discursiva e perpassado pelos níveis cognitivos e interacionais (JAGUARIBE, 2007; LIMA; CAVALCANTE, 2015; CAVALCANTE; BRITO, 2016). Por meio da análise do texto “Maria Maria”, mediante a perspectiva do discurso literomusical (COSTA, 2001), o segundo objetivo foi testar os limites atualmente evocados para a recategorização. Para testar esse limite e as potencialidades do processo de recategorizar, este ligado intimamente ao próprio ato de referir, foi estudado o referente “Maria” pelos aspectos macrossociais e investigados como e por que o objeto de discurso instaurado chega a representar, por meio da recategorização, grupos distintos, de lutas e de classes também distintas. Trata-se de uma abordagem que encontra ancoragem em outras pesquisas que estudam nomes próprios (CUSTÓDIO FILHO, 2011; BASSETTO, 2015; SOARES, 2018), mas que delas se distingue por observar um contexto de recategorização que transcende a constituição referencial inicial e passa a representar diferentes objetos do mundo.Palavras-chave: referenciação; recategorização; discurso literomusical.Abstract: The present study is born from two central objectives, which are retro nourished. The first is to discuss the current status of the theory of recategorization understood by the discursive dimension and run through by the cognitive and interactional levels (JAGUARIBE, 2007; LIMA; CAVALCANTE, 2015; CAVALCANTE; BRITO, 2016). Through the analysis of the text “Maria Maria”, seen from the perspective of the literature-musical discourse (COSTA, 2001), our second objective was to test the limits currently evoked for Recategorization. To test this limit and the potentialities of the process of recategorization, this linked intimately to the very act of referring, we study the referent “Maria” from the macro-social perspective and investigate how and why the object of discourse instituted comes to represent, through recategorization, distinct groups, of social struggles and distinct classes. It is an approach that finds support in other researches that study personal names (CUSTÓDIO FILHO, 2011; BASSETTO, 2015; SOARES, 2018), however distinguished from these, because we observe a context of recategorization that transcends the initial referential constitution and becomes able to represent different objects of the world.Keywords: referring; reclassification; literature-musical discourse.